The Impact of Different Intermittent Irrigation Management and Planting Distances on Yield and Yield Components of Rice Plant in Northern Iran - Kamyar Sabokrow Foomani; Saeed Sayfzadeh; Faramarz Ali Nia; Seyed Alireza Valad Abadi; Mohammadreza Yazdani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
In this study, a split plot experiment was conducted in a randomized complete blocks design with three iterations, for two years, in Gilan province (Iran), to investigate the impact of periodic irrigation and different planting distances on yield and yield components of rice plant. The irrigation was performed at five levels, I1, daily flooding irrigation (control treatment) and I2, I3, I4 and I5, every 5, 8, 10, and 15-days, respectively, as the main factor. Meanwhile, the planting distances were at four levels (S1: 20 × 20, S2: 25 × 25, S3: 15 × 30, and S4: 20 × 30 cm) as the sub factor. The simple effects of irrigation, as well as planting distance on all traits except harvest index, were significant at the level of 1%. In addition, the interaction of irrigation and planting distance on seed yield, plant height, number of seeds per panicle, biological yield, and water use were also significant at the level of 1%. The 20 × 20 planting distance resulted in the best conditions for the rice plant at different stress severities, thus, a 20 × 20 planting distance is appropriate in order to achieve good yield. Meanwhile, of the irrigation levels, 5-day irrigation led to the highest yield. The 5-day irrigation produced higher yield compared to flooding irrigation, and is therefore suitable for achieving higher yields as well as for water conservation, a major agricultural problem.